Hamzah Fansuri: Sastrawan dan Agamawan - Achadiati Ikram (HISKI, 2007)
Hamzah Fansuri is widely known through his sufi poetry, which is inseparable from the tasawuf school of Wahdat al-Wujud. Nevertheless, he also produced prose in the form of teaching in three of his works, i.e., Asrar al-Arifin, Syarab al-Asyiqin, and Al-Muntahi. This Paper explores Hamzah Fansuri’s thought in those works, which received Persian influence.